Peran Bimbingan Belajar AHE Tawangrejo dalam Meningkatkan Kemampuan Membaca Siswa Kelas Rendah - Shofria Ihda Mahayyun (Journal of Elementary Education Research, 2022)
This study aims to determine the role of the AHE (Great Children) tutoring institution of Tawangrejo in improving the reading ability of low-grade students. The government through Government Regulation Number 17 in 2010 concerning Management and Implementation of Education strictly prohibits the existence of tests as a requirement for acceptance of elementary school/Islamic elementary school students. The prohibition is contained in Article 69 paragraph 5 which said, "Acceptance of elementary school/Islamic elementary school students in first grade or other equivalent form is not based on the test results of reading, writing, and arithmetic or others test forms.” However, many parents are worried that their children who have been in 1st, 2nd, 3rd grade of Islamic elementary school have not been able to read. This is the reason why parents send their children to AHE Tutoring of Tawangrejo. This research is a field research with a descriptive qualitative approach. The results of this study are able to find out the implementation of learning in AHE Tutoring of Tawangrejo, the role of AHE Tawangrejo Tutoring in improving reading skills and the obstacles faced by AHE Tutoring of Tawangrejo.